Y=(-x*x)-4x+3
y=-(x^2+4x-3)
4+y=-(x^2+4x+4)+3
y+4=-(x-2)^2.) +3
-4. -4
y=-((x-2)^2)-1
Answers:
Vertex: (2,-1)
AOS:x = 2
Domain: All Real Numbers
Range:[-1,Infinity)
Solution Step1 Converting 112 to base 10.
1*82=64
1*81=8
2*80=2
Adding all to get Ans=7410 <span>Step2 converting 7410 to 2</span> The equation calculation formula for 7410 number to 2 is like this below.
2|74
2|37|0
2|18|1
2|9|0
2|4|1
2|2|0
2|1|0
2|1|1
<span>Ans:10010102</span>
The product of a number y and 12 or 12 times a number y. These are both equivalent expressions to 12y